SISTEM PEMANTAU KESEHATAN UNTUK PASIEN VIA USER DATAGRAM PROTOCOL (UDP) DAN LONG RANGE (LORA) - Hendry Rama Sethiawan; Ponco Siwindarto; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2023)
Recent advances in the Internet of Things (IoT) technology design are spurring the development of intelligent systems to support and enhance healthcare and biomedical-related processes. This study aims to design a health monitoring system for patients through UDP and LoRa and measure heart rate, blood oxygen saturation, ECG signal, and body temperature with a certain method. The methods used include the Photoplethysmogram (PPG) method to measure heart rate and blood oxygen saturation, the infrared reading method to measure body temperature and the 3-lead method to form an Einthoven triangle on the chest to read ECG signals. This system data transmission uses LoRa with a frequency of 923 MHz and Wi-Fi with a frequency of 2.4 GHz that utilizes the User Datagram Protocol (UDP). The results of this study are measurements of each sensor in measuring and sending data via LoRa and Wi-Fi. Keywords: Internet of Things (IoT), heart rate measurement, blood oxygen saturation measurement, ECG signal reading, body temperature measurement, LoRa, User Datagram Protocol (UDP)